Abstracts of Note: The Bioethics Literature - Iserson, Kenneth V. (Cambridge quarterly of healthcare ethics, 2006)
This section is meant to be a mutual effort. If you find an article you think should be abstracted in this section, do not be bashful—submit it for consideration to feature editor Kenneth V. Iserson care of CQ. If you do not like the editorial comments, this will give you an opportunity to respond in the letters section. Your input is desired and anticipated.